Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan - Yuliana Anggreani Dua Delang Kolit; Magdalena Nona Ice; Tobias Joni Temu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of tax knowledge and taxpayer awareness on taxpayer compliance in paying Land and Building Tax in Takaplager Village, Nita District. The research method used is primary data in the form of questionnaires distributed to taxpayers registered in Takaplager Village, Nita District. The sampling technique used the slovin formula with the number of questionnaires distributed as many as 88 respondents. The results showed that the variables of tax knowledge and taxpayer awareness had a significant effect on taxpayer compliance in paying land and building tax.